Optimalisasi Wakaf Tanah Perspektif Istibdal (Studi pada Harta Wakaf Pimpinan Daerah Muhammadiyah Kota Yogyakarta) - Yusuf, Muhammad Zulfikar (Jurnal Magister Ekonomi Syariah, 2022)
This study aims to analyze the optimization of waqf land in the perspective of istibdal carried out by the Muhammadiyah Regional Leadership of Yogyakarta City. The type of research used is descriptive qualitative research with interviews and literature study. The analytical method used is istihsan analysis by looking for benefits in the istibdal process of waqf property. Based on the results of the analysis carried out, it was found that istibdal waqf property is one way so that the benefits of waqf can continue to be felt on waqf assets that are no longer productive or cannot be used anymore. Istibdal waqf is needed as an effort so that the waqf property is still able to provide benefits as aspired by the wakif. There are four (4) types of istibdal waqf that have been used in exchanging waqf property, namely: Istibdal Nazhir, Istibdal Benefits, Istibdal Place and Istibdal Status. Istibdal land waqf carried out by PDM Yogyakarta City is able to optimize waqf land well. This is evident from the utilization of waqf land which has not been able to be maximized due to various obstacles then istibdal land waqf is carried out which is significantly able to make the waqf property optimal and productive again.